Determination of ethinylestradiol and levonorgestrel in oral contraceptives with HPLC methods with UV detection and UV/fluorescence detection - Zorica Arsova-Sarafinovska; Liljana Ugrinova; Katerina Starkoska; Dragan Djordjev; Aneta Dimitrovska (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2006)
Oral contraceptives are pharmaceutical formulations containing an estrogen in a small amount and a synthetic progestin in 5-30 times bigger amount. A sensitive, accurate and rapid method for determination of active compounds is required. We have developed HPLC methods for determination of ethinylestradiol (EED) and levonorgestrel (LNG) in commercially available tablets. Chromatographic separation was performed on a Purospher® STAR RP-18e reversed-phase column (150 X 4.0 mm I.D.; particle size 5 µm) in an isocratic mode with a mobile phase constituted of 47% acetonitrile: 53% water (V/V) for both methods. The elution was carried out at a flow rate of 1.50 ml /min. All analyses were performed at room temperature (24 +/- 2°C). In the HPLC method with UV detection (internal standard method) both compounds were detected at 215 nm. Drospirenone was used as an internal standard. In HPLC method with UV/fluorescence detection (external standard method) LNG was monitored at 242 nm, while EED was detected with fluorescence detector at 310 nm (excitation 285 nm). The methods' performances were fully validated by a determination of linearity, reproducibility, accuracy and sensitivity. Both methods were applied for determination of Uniformity of Dosage Units. The results obtained with both methods were highly comparable. However, the HPLC method with UV/ fluorescence detection has showed superior sensitivity for EED indicated by 83 times lower detection limit. HPLC method with UV/ fluorescence detection could be recommended as a method of choice for determination of ethinylestradiol, present at a very low dosage level in low-dose oral contraceptives, that also contain bigger amount of synthetic progestin.